2018
DOI: 10.1029/2018ea000400
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Geant4 for Simulating Galactic Cosmic Ray Interactions Within Planetary Bodies

Abstract: Galactic cosmic rays undergo complex nuclear interactions with nuclei within planetary bodies that have little to no atmosphere. Radiation transport simulations are a key tool used in understanding the neutron and gamma ray albedo coming from these interactions and tracing these signals back to geochemical composition of the target. We study the validity of the code Geant4 for simulating such interactions by comparing simulation results to data from the Apollo 17 Lunar Neutron Probe Experiment. Different assum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 58 publications
(142 reference statements)
1
10
0
Order By: Relevance
“…We also compared the neutron density versus the soil depth with the LNPE data collected during the Apollo 17 mission (Section 3.1) and found a similar scale factor as obtained by Mesick et al. (2018) when comparing the modeled results to the data using the same physics list FTFP_BERT_HP. The surface albedo neutron spectrum has also been compared with previous experimental (Lunar Prospector) and modeling results (Section 3.3).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…We also compared the neutron density versus the soil depth with the LNPE data collected during the Apollo 17 mission (Section 3.1) and found a similar scale factor as obtained by Mesick et al. (2018) when comparing the modeled results to the data using the same physics list FTFP_BERT_HP. The surface albedo neutron spectrum has also been compared with previous experimental (Lunar Prospector) and modeling results (Section 3.3).…”
Section: Discussionsupporting
confidence: 69%
“…Indeed, different physics lists can be chosen in GEANT4 for modeling the radiation environment in space. Mesick et al (2018) explored different physical models for calculating the lunar radiation environment and found some discrepancies in the resulting neutron flux (see more details in Section 3.1). Guo et al (2019) found that the Liège Intranuclear Cascade (INC) model has a higher efficiency in generating secondary particles using spallation processes in the energy range from a few GeV to about 20 GeV when modeling the Martian radiation environment.…”
Section: Geant4 Modelingmentioning
confidence: 99%
“…The simulation code was based on the Geant4 toolkit v.10.0 (Agostinelli et al, 2003; Allison et al, 2006). In particular, we used the physics list QGSP_BIC_HP (Quark‐Gluon String model for high‐energy interactions; Geant4 Binary Cascade model; High‐Precision neutron package) (Geant4 collaboration, 2013), which was shown to describe the cosmic ray cascade with sufficient accuracy (e.g., Mesick et al, 2018). We simulated a real‐scale spherical atmosphere with the inner radius of 6,371 km, height of 100 km and thickness of 1,050 g/cm 2 .…”
Section: Production Modelmentioning
confidence: 99%
“…Likewise, ω E is cos θ E . The gamma-ray or neutron current J (ω E ) from each of these facets is calculated using radiation transport modeling tools like MCNPX (e.g., McKinney et al 2006 ; Prettyman et al 2006 ) and Geant4 (e.g., Peplowski 2018 ; Mesick et al 2018 ). The number of gamma rays or neutrons emitted from facet at i is denoted j γ (ω E , ϕ E ) or j n (ω E , ϕ E ), respectively.…”
Section: Application Of the Megane Footprint To Phobosmentioning
confidence: 99%